Screening for Latent Tuberculosis Infection using Interferon-Gamma Release Assay Test among Healthcare Workers - Rosamarlina, Rosamarlina; Mariana, Nina; Sundari, Titi; Setianingsih, Tri Yuli; Jahiroh, Jahiroh; Pertiwi, Intan; Widiantari, Aninda Dinar; Setiawaty, Vivi; Murtiani, Farida (Universitas Islam Bandung, 2023)
Healthcare workers (HCWs) represent a significant demographic for screening latent tuberculosis infection (LTBI) due to their potential exposure to infectious patients. Tests based on immunology detection, such as the tuberculin skin test (TST) and the interferon-gamma release assay (IGRA), have been pivotal in diagnosing LTBI. The objective of this study was to evaluate the efficacy of the IGRA test in detecting LTBI compared to the TST among HCWs in an infectious disease hospital. In a cross-sectional study conducted in August 2019 at the Sulianti Saroso Infectious Disease Hospital, we examined 84 HCWs selected through consecutive sampling. Participants were assessed using questionnaires, and the IGRA and TST tests were performed. The findings revealed that 42 (50%) HCWs tested positive for LTBI based on the IGRA test. Most were female, aged 36–45 years, had direct exposure to TB patients, and had been in the healthcare profession for over a decade. The concordance between the TST and IGRA test, as indicated by a κ value, was 0.234. Furthermore, a significant correlation was observed between the incidence of LTBI and the duration of the healthcare profession (p=0.016). In conclusion, our research suggests that both TST and IGRA tests can effectively detect LTBI. The IGRA test had a higher positivity rate among HCWs with over ten years of service.